2007
DOI: 10.1590/s0066-782x2007001400014
|View full text |Cite
|
Sign up to set email alerts
|

Transplante de Células-tronco marcadas para o miocárdio de paciente com doença de chagas

Abstract: A 50-year old male individual with refractory heart failure secondary to dilated cardiomyopathy due to Chagas' disease was referred to our Institute that is authorized by the Brazilian Health Ministry to employ stem cell therapy for dilated cardiomyopathy, Chagas' disease and acute myocardial infarction.The myocardial perfusion study with 99 mTc SESTAMIBI showed large areas with low uptake in the anterior, apical and septal walls of the left ventricle (Fig. 1). Cardiac catheterization revealed severe left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…For instance, cardiac transplant is a procedure that has been applied and has demonstrated clinical benefit in some patients with terminal heart failure [78]. Stem cell transplant is a new therapy applied to produce cardiac regeneration through distinction or increase heart myocytes or neovascular proliferation in patients in the final stage of congestive heart failure [7981], but the results are still insufficient on Chagas disease, and there is no consensus about its efficacy [80]. …”
Section: Discussionmentioning
confidence: 99%
“…For instance, cardiac transplant is a procedure that has been applied and has demonstrated clinical benefit in some patients with terminal heart failure [78]. Stem cell transplant is a new therapy applied to produce cardiac regeneration through distinction or increase heart myocytes or neovascular proliferation in patients in the final stage of congestive heart failure [7981], but the results are still insufficient on Chagas disease, and there is no consensus about its efficacy [80]. …”
Section: Discussionmentioning
confidence: 99%
“…In a patient with chagasic cardiomyopathy, bone marrow mononuclear cells delivered by the intracoronary route were preferentially retained in diseased, hypoperfused areas of the myocardium [32]. Further studies using labeled cells confirmed these results (Barbosa, personal communication).…”
Section: Cell Therapy For Chagasic Cardiomyopathymentioning
confidence: 91%
“…O transplante de CTs acaba sendo uma nova terapia com objetivo de produzir regeneração cardíaca pela diferenciação ou aumento dos miócitos cardíacos ou proliferação neovascular em pacientes no estágio final de insuficiência cardíaca congestiva secundária a cardiomiopatia dilatada idiopática ou chagásica, na cardiopatia isquêmica crônica e no infarto agudo do miocárdio, dentre outras degenerações cardíacas. Porém, os resultados destas aplicações clínicas ainda são desconhecidos não perdendo seu potencial, mas não deixam de serem promissores e na maioria dos casos mostram um percentual regenerativo importante para pacientes submetidos à terapia (JACOB et al, 2007). Moreira et al (2011) descreveram o uso de injeção de CTs no Infarto Agudo do Miocárdio (IAM) sendo este um teste, quase exclusivo, da via anterógrada Intra-Arterial Coronariana (IAC).…”
Section: Uso Clínico Na Cardiologiaunclassified
“…No entanto, a circulação sanguínea na área de infarto pode ser gravemente afetada, dificultando o potencial acesso das células injetadas na área em que elas são necessárias para a reparação tecidual. Jacob et al (2007) apresentaram o uso de CTs através de injeção intracoronariana após infarto do miocárdio e procedimento de punções da crista ilíaca e uso dessas células para tratamento do estágio final de pacientes com cardiopatia dilatada. O caso relatado mostra que, após infusão de células mononucleares pela técnica intracoronariana, uma significativa quantidade dessas células é atraída para áreas previamente não funcionais do miocárdio e nelas retidas (provavelmente miocárdio fibrótico).…”
Section: Uso Clínico Na Cardiologiaunclassified